Retrospective analysis of 11 patients with ipsilateral hemiplegia caused by acute cerebral infarction - Huang, Lixian; Li, Hongyan; Hou, Xiaoying; Guo, Xiaoyuan; Zou, Yihuai (Frontiers in Neurology, 2025)
ObjectiveTo summarize the clinical and imaging characteristics of patients with ipsilateral hemiparesis caused by acute cerebral infarction, and to explore possible pathophysiological mechanisms.MethodsThis is a retrospective case series study. Clinical data of 11 patients with ipsilateral hemiparesis caused by acute cerebral infarction admitted to the Neurology Department, Dongzhimen Hospital, Beijing University of Traditional Chinese Medicine from January 1, 2021 to March 30, 2025 were collected. Descriptive analysis was conducted on the patients’ neurological symptoms and signs, magnetic resonance imaging (MRI), blood tests, and other examination results.ResultsAmong the 11 patients with acute cerebral infarction, the onset time was between 6 and 48 h. Nine patients did not undergo thrombolysis, two patients underwent thrombolysis, five patients had left hemiparesis, and six patients had right hemiparesis. There were 6 cases of hemiparesis with muscle strength level 4, 3 cases with muscle strength level 5−, 1 case with proximal muscle strength level 2 and distal muscle strength level 4, and 1 case with upper limb muscle strength level 4 and lower limb muscle strength level 3−. In terms of combining other neurological symptoms, there were 6 cases of speech impairment, 2 cases of hemihypesthesia, 3 cases of facial paralysi, and 4 cases without neurological symptoms. There were 10 cases of anterior circulation and 1 case of posterior circulation, involving infarcted areas such as thalamus, basal ganglia, corona radiata (adjacent to or centrum semiovale), frontal lobe, cerebral peduncle of midbrain, and responsible blood vessels involving involving large artery disease in 7 cases and perforating arteries in 4 cases. Based on the Chinese Ischemic Stroke Subclassification (CISS), the main etiological types are atherosclerosis, perforating artery disease, and other causes (cerebrovascular malformation).